Cocos nucifera Shell as a Potential Inhibitor for Mild Steel Corrosion in Acidic Medium - VIJAYALAKSHMI, P.R.; RAJALAKSHMI, R.; SUBHASHINI, S. (Asian Journal of Chemistry, 2010)
The effect of coconut (Cocos nucifera) shell extract obtained by destructive distillation, on the corrosion of mild steel in H2SO4 and HCl in the temperature range of 30-60° C was studied by weight loss method and electrochemical measurements. Results obtained reveal that the extract reduces the corrosion rate. The inhibition efficiency increases with an increase in the concentration of the extract and appreciable increase with increase in temperature. Experimental results were fitted into various adsorption isotherms. Activation energy and thermodynamic parameters were evaluated from temperature studies. Electrochemical measurements reveal that the extract behaves as a mixed type inhibitor. A suitable mechanism is also proposed.